2023
DOI: 10.1073/pnas.2220551120
|View full text |Cite
|
Sign up to set email alerts
|

Circadian clock protein BMAL1 broadly influences autophagy and endolysosomal function in astrocytes

Abstract: An emerging role for the circadian clock in autophagy and lysosome function has opened new avenues for exploration in the field of neurodegeneration. The daily rhythms of circadian clock proteins may coordinate gene expression programs involved not only in daily rhythms but in many cellular processes. In the brain, astrocytes are critical for sensing and responding to extracellular cues to support neurons. The core clock protein BMAL1 serves as the primary positive circadian transcriptional regulator and its d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…Bmal1 deletion in astrocytes leads to astrogliosis, with increased reactivity, autophagy/lysosomal degradation, and phagocytosis. 82,83 Rev-erbα-deficient microglia have a more variable response. There is increased reactivity, lipid droplet formation, and synaptic/Aβ phagocytosis; however, there is less extracellular Tau phagocytosis.…”
Section: Oligodendrocytesmentioning
confidence: 99%
See 2 more Smart Citations
“…Bmal1 deletion in astrocytes leads to astrogliosis, with increased reactivity, autophagy/lysosomal degradation, and phagocytosis. 82,83 Rev-erbα-deficient microglia have a more variable response. There is increased reactivity, lipid droplet formation, and synaptic/Aβ phagocytosis; however, there is less extracellular Tau phagocytosis.…”
Section: Oligodendrocytesmentioning
confidence: 99%
“…72 Bmal1 -deficient astrocytes show increased expression of lysosomal proteins and enhanced endocytosis in vitro. 82 Systemically, deleting Bmal1 in astrocytes causes metabolic imbalance, disrupted glutamate and GABA levels, and decreased life span. 88 In mouse models of tau and alpha-synuclein proteinopathy, astrocyte-specific Bmal1 deletion can increase macroautophagy and mitigate toxic protein aggregation (Figure 2).…”
Section: Glial Clocksmentioning
confidence: 99%
See 1 more Smart Citation
“…124 In the SCN, rhythms in astrocyte function regulate excitatory glutamatergic signaling 124,125 and inhibitory GABAergic signaling, 126,127 ultimately altering cellular metabolism and glucose homeostasis throughout the body. 127,128 Beyond the SCN, loss of BMAL1 in astrocytes leads to reactive gliosis, endosomal dysfunction, and altered homeostasis of amyloid-β within the CSF, 129–132 and astrocytes may undergo daily morphological changes. 133 Apart from genetic models of circadian clock disruption, the primary evidence for astrocytic regulation of circadian rhythms comes from studies of astrocytes in sleep.…”
Section: Rhythms In Csf Pathways: the Glymphatic And Lymphatic Systemsmentioning
confidence: 99%
“…Recent studies have linked BMAL1 to protein degradation in astrocytes within the brain. McKee et al (2023) demonstrated that deleting Bmal1, specifically in astrocytes, leads to a unique cell-autonomous activation state. This activation phenotype not only disrupts circadian function but also hampers the supportive role of astrocytes to neurons while simultaneously increasing extracellular protein degradation ( McKee et al, 2023 ).…”
Section: Role Of Astrocytes In Sd-comorbid Brain Disordersmentioning
confidence: 99%